Radiofrequency ablation and endoscopic resection in a single session for Barrett’s esophagus containing early neoplasia: a feasibility study - van Vilsteren, F. G. I.; Alvarez Herrero, L.; Pouw, R. E.; Visser, M.; ten Kate, F. J. W.; van Berge Henegouwen, M. I.; Schoon, E. J.; Weusten, B. L.; Bergman, J. J. (Endoscopy, 2012)
Background and study aim: Endoscopic resection with radiofrequency ablation (RFA) 6 weeks later safely and effectively eradicates Barrett’s esophagus with high grade dysplasia (HGD) and early cancer. After widespread endoscopic resection, related scarring may hamper balloon-based circumferential RFA (c-RFA). However c-RFA immediately followed by endoscopic resection in the same session might avoid the impact of scarring and reduce laceration and stenosis risk. We aimed to assess the feasibility of such an approach. Patients and methods: Patients with Barrett’s esophagus ≥ 3 cm and ≥ 1 visible lesion (HGD/early cancer) were included. Visible lesions were marked with cautery, and c-RFA (12 J/cm2) was delivered using two applications and a cleaning step, followed by resection of the delineated area. Outcome measures were surface regression of Barrett’s esophagus at 3 months, need for subsequent c-RFA, complications, and quality of resection specimens. Results: 24 patients (20 men, 4 women; mean age 68 years, standard deviation [SD] 12; Barrett’s esophagus median length C6M8) underwent single-session c-RFA + endoscopic resection, providing a median of 4 (interquartile range [IQR] 2 – 6) resection specimens (early cancer 18 patients; HGD 6). Complications included 1 perforation, 4 bleedings, and 5 stenoses; all were managed endoscopically. Specimens allowed assessment of neoplasia depth, differentiation, and lymphatic/vascular invasion. Median Barrett’s esophagus surface regression at 3 months was 95 %. No patient required a second c-RFA procedure and 40 % required repeat endoscopic resection for visible lesions. Complete response for neoplasia was achieved in 100 % and complete response for intestinal metaplasia (CR-IM) in 95 %. Conclusions: c-RFA followed by endoscopic resection in the same session is feasible, but technically demanding and associated with a substantial rate of complications and repeat endoscopic resection. This approach should be reserved for selected cases in expert centers, with endoscopic resection and RFA 6 – 8 weeks later remaining the standard combined approach.